2007
DOI: 10.1002/elsc.200700004
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antagonism of Rhizobacteria Isolated from Coffea arabica L. against Emerging Fungal Coffee Pathogens

Abstract: In vitro antagonistic effects of rhizobacteria associated with Coffea arabica L. against some fungal coffee pathogens were studied. The aims were to screen indigenous coffee‐associated isolates for their inherent antagonistic potential against major coffee wilt diseases induced by Fusarium spp. Antagonistic effects, siderophore, HCN and lytic enzyme production were determined on standard solid media. Chemical methods were employed to categorize the major types of siderophores. From a total of 212 rhizobacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…isolated from different plant species were the most abundant rhizobacteria showing in vitro antagonism against V. dahliae, with their diversity being both site-and plant-specific (Berg et al 2002(Berg et al , 2005b. Recently, Muleta et al (2007Muleta et al ( , 2009, screened the in vitro antagonistic effect of indigenous cultivable rhizobacteria associated with Coffea arabica, and found that most bacteria showing inhibitory activity against growth of Fusarium spp. were members of Pseudomonas and Bacillus spp.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…isolated from different plant species were the most abundant rhizobacteria showing in vitro antagonism against V. dahliae, with their diversity being both site-and plant-specific (Berg et al 2002(Berg et al , 2005b. Recently, Muleta et al (2007Muleta et al ( , 2009, screened the in vitro antagonistic effect of indigenous cultivable rhizobacteria associated with Coffea arabica, and found that most bacteria showing inhibitory activity against growth of Fusarium spp. were members of Pseudomonas and Bacillus spp.…”
Section: Discussionmentioning
confidence: 98%
“…to inhibit growth of pathogenic fungi is well known and these bacteria have been reported to be one of the most frequent beneficial rhizobacteria showing broad antifungal effect (Muleta et al 2007). In culturedependent studies, Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…The enzymes are usually for defence and they could be cell walldegrading hydrolytic enzymes. The production of enzymes includes chitinase, cellulase, b-1,3-glucanase, protease, lipase can lyse some fungal cells (Muleta et al 2007) and suppress deleterious rhizobacteria. Examples of the best characterized defence enzymes are peroxidase, polyphenol oxidase and phenylalanine ammonia-lyase (Latha et al 2009).…”
Section: Release Of Enzymesmentioning
confidence: 99%
“…Pseudomonas spp. that showed remarkable inhibitory effects against the test fungal pathogens produced HCN (Muleta et al, 2007). This compound, although reported as a potential inhibitor of enzymes involved in major plant metabolic processes (Bakker and Schippers, 1987) is currently attracting remarkable attention and wide applications in areas of biocontrol methods.…”
Section: Assay For Hydrogen Cyanide Productionmentioning
confidence: 99%